The Universal Credit (Miscellaneous Amendments, Savings and Transitional Provision) Regulations (S.I. 2018 No. 65) : Report by the Social Security Advisory Committee under Section 174(1) of the Social Security Administration Act 1992 and statement by the Secretary of State for Work and Pensions in accordance with Section 174(2) of that Act.: Report by the Social Security Advisory Committee under Section 174(1) of the Social Security Administration Act 1992 and statement by the Secretary of State for Work and Pensions in accordance with Section 174(2) of that Act. (January 2018) - Great Britain., Social Security Advisory Committee,
No abstract available